Universal software safety standard. - Bhansali, P. V. (Software engineering notes.)
This paper identifies the minimum subset required for a truly universal safety-critical software standard. This universal software standard could be used in but is not limited to the following application domains: commercial, military and space aviation; medical diagnostic and therapeutic instruments; automotive and transportation systems; industrial process control and robotics; nuclear power plants and weapons control; commercial appliances and ride electronics. The standard takes into account that safety is a system attribute but focuses on software as the critical component. Its roots are based in MoD 00-55, 56, DO-178B, ARP 4754 and 4761, Mil-Std-882 and Software Safety Handbook, IEC 61508, IEC 60880, ANSI/ISA-S84.01, ANSI/AAMI SW68:2001, NASA-STD-8719.13, UL 1998, EN 50128, MISRA Automotive Standard, and IEEE 1228. This minimum subset uses existing system and software technology and can be adapted to future applications. A universal software safety standard would benefit the entire safety-critical industry by lowering the cost and improving the quality of software by having common processes and tools. As an additional benefit, various application sectors could share data on the efficacy of each technique used in the development and verification of safety-critical software. This in turn could improve the overall safety of systems in the future.